Does peer monitoring influence choices between cash and food? Findings from a field experiment. (December 2016) - Lentz, Erin; Ouma, Robert; Mude, Andrew
Highlights: In this northern Kenyan field experiment, we examine how peer monitoring shapes choices. Respondents choose among monetarily equivalent goods in public or in private. Choosing in front of peers increases the likelihood of choosing at least some food. We argue that monitoring changes the relative value of cash and food. Abstract: To explore whether choices for transfers are influenced by peer monitoring, we examine private versus public choices among monetarily equivalent values of cash and food in northern Kenya. Many northern Kenyan communities face high-levels of chronic food insecurity and are tightly-knit, often sharing food aid transfers. Yet, humanitarian cash transfers are relatively new to the area. Whether cash will be subject to the same sharing norms is not well understood. Utilizing a randomized block experiment, we find that assigning a respondent to choose in front of peers decreases the likelihood of choosing a cash transfer relative to at least some food. We argue that peer monitoring decreases the value of cash relative to food in two inter-related ways. Choosing food in public, first, provides an opportunity for respondents to publicly demonstrate a commitment to local food aid sharing norms. Second, choosing cash in public may be riskier since cash does not yet have established sharing norms. A critical implication is that transfer choices and retargeting of resources within the community can be influenced by use of public or private discussions when eliciting community views, especially in communities where sharing is a salient social norm.